America's allies and war : Kosovo, Afghanistan, and Iraq - Davidson, Jason (New York : Palgrave Macmillan, 2011)
"Why do Britain, France, and Italy provide or refuse military support for U.S.-led uses of force? This book provides a unique, multiple-case study analysis of transatlantic burden-sharing. Sixty original interviews with top policymakers and analysts provide insight into allies' decisions regarding the Kosovo War (1999), Afghanistan (2001), and the Iraq War (2003). The cases show that neoclassical realist factors--alliance value, threat, prestige, and electoral politics--explain allies' decisions better than constructivist factors--identity and norms. The book briefly covers additional cases (Vietnam, Lebanon, the Persian Gulf War, Somalia) and concludes with recommendations for increasing future allied military support"--Provided by publisher.
Machine generated contents note: Transatlantic Alliance Burden-sharing: Defining and Justifying the Question * A Neoclassical Realist Explanation of Transatlantic Alliance Burden-sharing * Vietnam, Lebanon, Persian Gulf, and Somalia * Kosovo * Afghanistan * Iraq * Improving Transatlantic Alliance Burden-sharing.
Machine generated contents note: Transatlantic Alliance Burden-sharing: Defining and Justifying the Question * A Neoclassical Realist Explanation of Transatlantic Alliance Burden-sharing * Vietnam, Lebanon, Persian Gulf, and Somalia * Kosovo * Afghanistan * Iraq * Improving Transatlantic Alliance Burden-sharing.
Includes bibliographical references and index.
Keywords: Alliances -- Case studies; World politics -- 1989-; United States -- Military relations -- Europe; Europe -- Military relations -- United States; United States -- Military relations -- Europe -- Case studies; Europe -- Military relations -- United States -- Case studies